Sermons as a Formation of Ethical Behavior of Man in the Second Half of the 18th Century, Based on the Example of Sermons by Dominik Mokoš OFM (1718-1776) - Škovierová, Angela (Vox Patrum, 2023)
Dominik Mokoš (1718–22.XII.1776) was a Franciscan monk and religious writer who also acted as preacher, vicar, teacher and chronicler in the second half of the 18th century in various regions of Slovakia (such as Nižná Šebastová, Stropkov, Kremnica, Pruské, Okoličné, Beckov) or as a missionary in various areas of Šariš, Spiš, Orava and Poland. He was one of the most prolific authors of homiletic literature in the second half of the 18th century in Slovakia. In his Marian, Christmas and lenten preaching, we can identify intertextual references to the Bible, patristic, medieval and humanist religious literature. This study focuses on how these sources were used by Mokoš to draft his sermons and how he applied their moral tidings to the particular situations that the believers in the 18th century were facing.